Performance properties of irradiated recycled polypropylene as a compatibilizer in recycled polypropylene/microcrystalline cellulose composites - Samat, Noorasikin; Mohd Lazim, Nurul Hakimah; Motsidi, Siti Nor Rasyidah; Hassan, Noor Azlina (2016)
Effects of irradiated rPP compatibilizer on the mechanical and thermal properties of recycled polypropylene/microcrystalline cellulose composites (rPP/MCC) have been investigated. The rPP were irradiated with an electron beam with dosages ranging from 10, 20, 30 and 50kGy. Matrix containing of unirradiated and irradiated rPP (50:50 by ratio) was then added with 5, 20 and 40wt% MCC fibers. The composites were prepared by using a twin screw extruder followed by injection molding and the properties were characterized with tensile and thermal degradation tests. The improvement of Young’s modulus up to about 45% suggests the compatilizing effect of irradiated rPP. Fracture surface observations reveal an adhesion between rPP matrix and MCC fibers. However, the thermal stability deteriorated with the addition of MCC and irradiation rPP.